A poética do video game: um estudo do potencial estético dos jogos digitais casuais - Filipe Alves de Freitas (2015)
There is a controversy about the possible artistic status of the video game: one side argues that the medium will never be regarded as an artistic form due to properties such as its interactivity and its affinity with sports; the other affirms a possible artistry to the medium by sacrificing its game quality. Prompted by this unresolved disagreement, I propose to investigate in this research if video games can provide aesthetic experiences not despite the fact that they are games, but because they are games. Therefore, I seek to develop, by articulating the theories of John Dewey, Wolfgang Iser and Luigi Pareyson, a conceptualization of aesthetic experience that can account for the particular characteristics of the medium and provide criteria for the study of the corpus a set of casual digital games classified as "interactive art" by the aggregator website Casual Gameplay so that, based on this analysis, I can formulate the foundations of an aesthetic theory of the medium: the Poetics of Video Game.